A continental perspective on the timing of environmental change during the last glacial stage in Australia. (July 2021) - Cadd, Haidee; Petherick, Lynda; Tyler, Jonathan; Herbert, Annika; Cohen, Tim J; Sniderman, Kale; Barrows, Timothy T.; Fulop, Reka H.; Knight, Jasper; Kershaw, A. Peter; Colhoun, Eric A.; Harris, Mathew R.P.
Abstract: The timing and duration of the coldest period in the last glacial stage, often referred to as the last glacial maximum (LGM), has been observed to vary spatially and temporally. In Australia, this period is characterised by colder, and in some places more arid, climates than today. We applied Monte-Carlo change point analysis to all available continuous proxy records covering this period, primarily pollen records, from across Australia (n = 37) to assess this change. We find a significant change point occurred (within uncertainty) at 28.6 ± 2.8 ka in 25 records. We interpret this change as a shift to cooler climates, associated with a widespread decline in biological productivity. An additional change point occurred at 17.7 ± 2.2 ka in 24 records. We interpret this change as a shift towards warmer climates, associated with increased biological productivity. We broadly characterise the period between 28.6 (± 2.8) – 17.7 (± 2.2) ka as an extended period of maximum cooling, with low productivity vegetation that may have occurred as a combined response to reduced temperatures, lower moisture availability and atmospheric CO2 . These results have implications for how the spatial and temporal coherence of climate change, in this case during the LGM, can be best interrogated and interpreted.